Petrography of Sandstone Units of Injana Formation in Al-Teeb Area South Eastern Iraq - Kattoof Jasim, Hasan; Omer Ali, Maysoon (ASJ - Academic Science Journal, 2025)
AbstractThe present study deals with study the sandstone units of injana formation in Alteeb area, east of Missan governorate southeastern Iraq. Ten samples of these sandstone were collected in order thin sectined for petrogtaphic decribtion. these sandstone are composed from quartz (both monocrystalline and polycrystalline), feldspar (potash feldspar and plagioclase feldspar), and rock fragments (sedimentary, igneous, and metamorphic rock fragmentd), the sedimentary rock fragments composed from; carbonate, chert, old sandstone, mudstone, and evaporate rock fragments. Three types of cement will observe these are: carbonate, evaporate, and iron oxide cement.These sandstone classify as litharenite, sedarenite, and calclithite, dure to the predominant of carbonate rock fragment. These sandstone chimachaly and michanicaly unstable due to low percentage of stable componants (quarts and chert).Tectonically the Injana Formation was deposited under convergent plate boundaries: lithic recycled and transitional recycled conditions